2018
DOI: 10.1021/acs.molpharmaceut.8b00393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Therapeutic Potential of a HER3-Binding Affibody Construct TAM-HER3 in Comparison with a Monoclonal Antibody, Seribantumab

Abstract: Human epidermal growth factor receptor type 3 (HER3) is recognized to be involved in resistance to HER-targeting therapies. A number of HER3-targeting monoclonal antibodies are under clinical investigation as potential cancer therapeutics. Smaller high-affinity scaffold proteins are attractive non-Fc containing alternatives to antibodies. A previous study indicated that anti-HER3 affibody molecules could delay the growth of xenografted HER3-positive tumors. Here, we designed a second-generation HER3-targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
4
24
1
Order By: Relevance
“…The anti-HER3 affibody molecules also demonstrated cross-species reactivity with the murine HER3 counterpart, mErbB3 (31), and murine models would therefore reflect the factors influencing the distribution of the anti-HER3 affibody molecules in humans. In preclinical therapy studies, treatment of mice with a construct containing two anti-HER3 affibody molecules (600 µg/injection, 3 injections/week) up to 70 days was not associated with any toxicity (32,33).…”
Section: Evaluation Of a Radiocobalt-labelled Affibody Molecule For Imentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-HER3 affibody molecules also demonstrated cross-species reactivity with the murine HER3 counterpart, mErbB3 (31), and murine models would therefore reflect the factors influencing the distribution of the anti-HER3 affibody molecules in humans. In preclinical therapy studies, treatment of mice with a construct containing two anti-HER3 affibody molecules (600 µg/injection, 3 injections/week) up to 70 days was not associated with any toxicity (32,33).…”
Section: Evaluation Of a Radiocobalt-labelled Affibody Molecule For Imentioning
confidence: 99%
“…Many more potential drug candidates are in preclinical evaluation. Additionally, we have recently demonstrated that an anti-HER3 affibody dimer fused with a domain with high affinity to albumin, Z HER3 -ABD-Z HER3 , inhibited HER3-induced phosphorylation in vitro and delayed growth of HER3 expressing tumours in vivo (32,33). The fact that 57 Co-Z HER3 binds to the same epitope as the anti-HER3 therapeutic agents seribantumab (47) and the affibody conjugate Z HER3 -ABD-Z HER3 (32) makes it appropriate to use this conjugate to monitor receptor occupancy during therapy.…”
Section: Du145 Ls174t -----------------------------------------------mentioning
confidence: 99%
“…Indeed, in vitro the bi- and trivalent HER3-specific affibody molecules were significantly more efficient in blocking phosphorylation of HER3 and inhibiting cellular activity and proliferation compared to the monovalent control [ 20 , 26 ]. We demonstrated that a bivalent construct based on an anti-HER3 affibody molecule fused with ABD, 3A3, also efficiently inhibited growth of HER3-expressing cells in vitro, had prolonged in vivo half-life, delayed growth of HER3-expressing BxPC-3 xenografts in mice, and was equipotent to seribantumab (MM-121) [ 27 , 28 ]. Importantly there was no observable toxicity after multiple administrations of the construct [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For therapeutic applications solely based on blocking the activity of tumour-related target protein as a mechanism of action, the fragment crystallisable (Fc) region of mAbs mediating, for instance, complement-dependent cytotoxicity and antibodydependent cell-mediated cytotoxicity (ADCC) is not required and might even be undesired 21 . Similar to non-Fc-portion antibody derivatives, such as scFv, fragment variable (Fv), and fragment antigen binding (Fab), affibody molecules are very valuable alternatives for such indications, and several affibody-based tumour targeting therapeutic agents with robust biological activity and no immunogenicity issues have been reported 30,38,39 . Affibody molecules do not contain any disulphide bridges, an observation suggesting that they could fold in the reducing environment of the cell cytoplasm 40 .…”
Section: Discussionmentioning
confidence: 99%